Diversity of piroplasmids among wild and domestic mammals and ectoparasites in Pantanal wetland, Brazil - de Sousa, Keyla Carstens Marques; Fernandes, Marina Pugnaghi; Herrera, Heitor Miraglia; Freschi, Carla Roberta; Machado, Rosangela Zacarias; André, Marcos Rogério (Elsevier, 2017)
Piroplasmoses are one of the most prevalent arthropod-borne diseases of animals. The present work aimed to investigate the occurrence of piroplasmid in wild mammals, domestic dogs and ectoparasites in southern Pantanal region, central-western Brazil. For that purpose, blood or tissue samples from 31 Nasua nasua, 78 Cerdocyon thous, 7 Leopardus pardalis, 42 dogs, 110 wild rodents, and 30 marsupials, and 1582 ticks were submitted to PCR assays for piroplasmid targeting 18SrRNA and hps70 genes. Seven dogs, one C. thous, five L. pardalis, three N. nasua, six wild rodents, eight Amblyomma parvum, two Amblyomma sculptum and one Amblyomma ovale were positive for piroplasmid-PCR assays. Genotypes closely related to Babesia vogeli were detected in six dogs and five wild rodents. While genotypes closely related to Babesia caballi were detected in one C. thous, one dog, one A. ovale and one A. sculptum, genotypes closely related to Babesia bigemina and Babesia bovis were detected in four A. parvum ticks. Four sequences obtained from A. parvum, three coatis and one wild rodent were closely related to Theileria equi. Cytauxzoon spp. was detected in four ocelots. The present study revealed that wild and domestic animals in Brazilian southern Pantanal are exposed to different piroplasmid species.
Keywords: Babesia; Cytauxzoon; Dogs; Phylogenetic analysis; Rangelia; Theileria; Wildlife